Effects of trail disturbance on native and non-native coastal prairie bunchgrass in Santa Cruz - Justin C Luong; Elisha Villanueva; Tori A Bauman (PANGAEA, 2022)
A data set containing measurements from two native and two non-native bunchgrass species that experienced and did not experience disturbance along dirt foot trails taken from five different coastal prairies in Santa Cruz, CA in 2019 and 2020. We examined how trail disturbance affects the vegetative growth and reproductive output of in situ native (Danthonia californica Bol. and Stipa pulchra Hitchc.) and non-native (Dactylis glomerata L. and Holcus lanatus L.) perennial bunchgrasses.